Development Of Infographic Poster Media In Biodiversity Learning To Improve Critical Thinking Skills Of High School Students - Jepril (International journal of technology and education research, 2025)
This research aims to develop learning media in the form of interactive infographic posters on Biodiversity materials to improve the critical thinking skills of high school students. The method used is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The subject of the study was a student of class XI Social Studies at SMA Negeri 1 Kotabunan. The validation results showed that the media included in the category was very valid with an average score above 90%. The results of the effectiveness test using N-Gain showed an increase of 0.72 (high category), while the Paired Sample t-test produced a p-value of 0.000 < 0.05 which indicates a significant increase in students' critical thinking skills after using media. Observation of student activities also showed excellent response with an average score of 3.7 (92.5%). Thus, the interactive infographic poster is declared valid, practical, and effective and feasible to be used as an alternative innovative learning media to support Geography learning and strengthen critical thinking skills according to the demands of the Independent Curriculu..